Essays on housing and pensions. A European perspective. - Müller, Thomas (Springer Gabler, 2019)
Demographic trends put a burden on EU pension provision. As the sustainability of pension systems is addressed by current pension reforms, lower benefit levels are projected. In this scenario, households may want to consider supplementing their public pension income. As their own residence is on average their most valuable asset, its transformation to income can be one form of alleviating financial distress in old age. The author presents research findings on the interdependency of housing and pension wealth as well as on whether and to what extent housing wealth is decumulated after retirement. The author emphasizes the consideration of housing wealth in pension policies to enable European households to employ its housing asset as an income source in old age.
Keywords: Wohnungswesen; Bevölkerungsentwicklung; Alter Mensch; Pension; Rente; Wohneigentum; Altersvorsorge; Vermögen; Umwandlung; Einkommen; Ökonometrie; EU; Alterseinkommen; Einkommensquelle; Altersarmut